The critical role of the adrenal gland in the renal regulation of acid-base equilibrium during chronic hypotonic expansion. Evidence that chronic hyponatremia is a potent stimulus to aldosterone secretion. - Cohen, J J (1976)
Recent studies have shown that chronic hypotonic volume expansion (HVE) induced by administration of vasopressin and water stimulates distal hydrogen ion secretion and thereby (a) permits dogs with HCl-acidosis to restore acid-base equilibrium to normal despite continued acid feeding and (b) permits normal dogs to conserve filtered bicarbonate quantitatively despite the natriuresis induced by water retention. To examine whether these effects of chronic HVE are mediated by augmented mineralocorticoid secretion, urinary and plasma aldosterone levels were monitored during prolonged administration of vasopressin. In HCl-fed animals, the HVE-induced rise in plasma [HCO3] (from 13.8 to 21.3 meq/liter) was associated with a rise in aldosterone excretion from 0.45 to 0.88 mug/day (P less than 0.02). In normal animals, in which plasma [HCO3] remained stable during HVE (21.9 vs. 20.0 meq/liter), aldosterone excretion rose from 0.51 to 2.28 mug/day (P less than 0.02) and plasma aldosterone concentration rose from 8.1 to 39.8 ng/100 ml (P less than 0.01). Vasopressin and water were also administered to adrenalectomized animals maintained on glucocorticoids and a slightly subphysiologic replacement schedule of mineralocorticoids. In the HCl-fed adrenalectomized group, plasma [HCO3], instead of rising to normal, showed no significant change (16.9 vs. 15.0 meq/liter). In the non-HCl-fed adrenalectomized group, plasma [HCO3], rather than remaining stable, fell significantly (20.3 vs 16.5 meq/liter, P less than 0.1). Two conclusions can be drawn from this study: (a) the well-known inhibitory effect of volume expansion on aldosterone secretion can be overridden by a potent stimulatory effect on the adrenal produced by severe chronic hypotonicity, and (b) the response of plasma [HCO3] observed during severe chronic HVE is mediated by augmented mineralocorticoid secretion. These findings, furthermore, offer a possible explanation for the puzzling observation that plasma [HCO3] in patients with the syndrome of inappropriate antidiuretic hormone secretion is maintained at normal levels even in the face of severe hyponatremia.